Television production assistant - Heath, David 1948- (Mankato, Minn. : Capstone High/Low Books, 1999)
Describes the position of television production assistant, covering the education and training requirements, duties, salary, and employment outlook.
Includes bibliographical references (p. 45) and index.
Keywords: Television -- Production and direction -- Vocational guidance -- Juvenile literature; Television -- Production and direction -- Vocational guidance; Vocational guidance